Splenogonadal fusion in a female: A case report of a rare congenital anomaly - Sara Elaish M.K. Mohamed, MBBS, MD; Mohamed F. Elawad, MD; Maysa A. Mohamed, MD; Sheik Akbar Hussain, MD; Amal A. Al-Rashid, MD (Radiology Case Reports, 2024)
We present a case of an 18-year-old female referred for an MRI pelvis to evaluate suspected uterine anomaly by ultrasound. The MRI showed a complete septate uterus and in addition, an elongated tubular structure (isointense to the spleen) extending from the left ovary in the left retroperitoneal region/left paracolic gutter to the under-splenic surface. CT abdomen and pelvis revealed this to be a similarly enhancing structure as the spleen and appears as a tubular retroperitoneal structure connecting the left ovary to the spleen with associated vasculature joining the splenic vein cranially and the ovarian vessels caudally consistent with splenogonadal fusion.